2018
DOI: 10.1242/dev.156554
|View full text |Cite
|
Sign up to set email alerts
|

NFIA and GATA3 are crucial regulators of embryonic articular cartilage differentiation

Abstract: During appendicular skeletal development, the bi-potential cartilage anlagen gives rise to transient cartilage, which is eventually replaced by bone, and articular cartilage which caps the ends of individual skeletal elements. While the molecular mechanism that regulates transient cartilage differentiation is relatively better understood, the mechanism of articular cartilage differentiation has only begun to be unraveled. Further, the molecules that coordinate articular and transient cartilage differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The most commonly expressed genes specific to the Lgr5 + bulk dataset included transcription factors ( Glis1 , Barx2 , and Pknox2 ) and ECM proteins ( Cilp and Col22a1 ). Several transcription factors reported to be related to joint formation were either specifically or more strongly expressed in Lgr5 + cells from the digit joint, such as Gata3 (Singh et al., 2018), Barx1/2 (Makarenkova and Meech, 2012), Irx1/2 (Zulch et al., 2001), and Sox5/6 (Dy et al., 2010) (Figure S3E and Tables S1–S3). Known pathways regulating interzone differentiation such as WNT, TGFβ, and MAPK (Decker et al., 2014, Gunnell et al., 2010) are also enriched in our Lgr5 + dataset (Figure S3F and Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly expressed genes specific to the Lgr5 + bulk dataset included transcription factors ( Glis1 , Barx2 , and Pknox2 ) and ECM proteins ( Cilp and Col22a1 ). Several transcription factors reported to be related to joint formation were either specifically or more strongly expressed in Lgr5 + cells from the digit joint, such as Gata3 (Singh et al., 2018), Barx1/2 (Makarenkova and Meech, 2012), Irx1/2 (Zulch et al., 2001), and Sox5/6 (Dy et al., 2010) (Figure S3E and Tables S1–S3). Known pathways regulating interzone differentiation such as WNT, TGFβ, and MAPK (Decker et al., 2014, Gunnell et al., 2010) are also enriched in our Lgr5 + dataset (Figure S3F and Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…A recent research showed that NFIA is colocalized with peroxisome proliferators‐activated receptor γ and regulates the transcription of the brown fat genes (Hiraike et al, 2017). More recently, it was demonstrated that NFIA‐ and GATA‐binding protein 3 regulated the differentiation of embryonic articular cartilage in chick (Singh et al, 2018). In the current study, our results indicate that NFIA overexpression reduced ALP staining and downregulated the mRNA expression of osteogenic markers, indicating that NFIA negatively regulated osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Parathyroid hormone-related protein (PTHrP encoded by PTHLH) is a key regulator of transitional chondrocytes and is secreted by articular chondrocytes and perichondrium cells. PTHrP was reported to maintain the continuous proliferation of chondrocytes and inhibit their terminal differentiation into hypertrophic chondrocytes after mitosis (Pelosi et al 2013;Singh et al 2018). One study has also shown that the partial regulatory effect of ERG on chondrocytes is mediated by PTHrP (Okabe et al 2011).…”
Section: Introductionmentioning
confidence: 99%